Gross Motor Coordination: We Have a Problem! A Study With the Körperkoordinations Test für Kinder in Youth (6–13 Years) - Giuriato, Matteo; Biino, Valentina; Bellafiore, Marianna; Battaglia, Giuseppe; Palma, Antonio; Baldari, Carlo; Guidetti, Laura; Gallotta, Maria Chiara; Schena, Federico; Lanza, Massimo (Frontiers in Pediatrics, 2021)
The main goal of our cross-sectional research was to verify the current values of Gross Motor Coordination (GMC) of Italian boys and girls between 6 and 13 years of age. Secondary goals were to study genders differences and the four subtests trend with ages. Results were compared with the references proposed by KTK Authors and with similar searches. Anthropometric measurements and KTK data from 2206 schoolchildren (Females: n=1050; Males: n=1156) were collected. KTK Raw score (RS) increased with the age of the subjects (r=.678; p<.001) progressively reducing, however, the increase and showed differences by gender (F=5.899; p=.015) and age (F=269.193; p<.001) without interaction gender x age. Motor Quotient (MQ) tended to decrease with age (r = -.148; p <.001); it showed differences by gender (F=79.228; p <.001), age (F=14.217; p <.001) and an interaction gender x age (F=2.249; p <.05). Males showed better performance than girls in the raw scores of three of four sub-tests (JS: F=24.529; MS: F=9.052; HH: F=11.105). Girls show better performances than boys in the WB (F =14.52). Differences between genders make us believe it appropriate to maintain a differentiated standardization. As was expected, RS increased with age and it seems reasonable, therefore, to maintain a GMC age-based normalization. On the contrary, MQ tended to decrease. All this makes us speculate that today's young people accumulate less significant motor experiences over the years compared to those achieved by their peers in the 1970s. Italian data were lower than German references and Belgian results but slightly higher than the Brazilian ones. The comparison among these four searches confirmed a worrying downward trend in GMC and its characterization by geographical and socio-cultural areas. Updated parameters of the KTK can provide helpful references to improve policies to support physical activity, sport and physical education in youth.